Characterizing diversity and variation in fish choruses in Darwin Harbour - Parsons, Miles; Salgado-Kent, C.; Marley, S.; Gavrilov, A.; McCauley, R. (Oxford University Press 2009, 2016)
© 2016 International Council for the Exploration of the Sea. All rights reserved.The diversity, intensity, and periodicity of fish sounds can provide a wealth of information on spatial and temporal distribution of soniferous fish and, on occasion, which environmental factors these choruses are driven by. Such information can help predict species presence and understand their movement patterns in the long term. At three sites in Darwin Harbour, Australia, sea-noise loggers on the harbour floor recorded ambient noise over a 2-year period. Many fish calls and nine different chorus types were detected over 50 Hz to 3 kHz. Source species were speculated for four of the choruses and source levels, a precursor to passive acoustic abundance estimates, were identified for two of these. Other calls displayed similarities to choruses detected elsewhere in Australia. All choruses displayed diel cycles with semi-lunar patterns present for three of the chorus types. Time of sunset and temperature were also significantly related to the presence of the most predominant chorus and while not statistically significant, height of high tide and salinity also appeared related. A lack of frequency and temporal partitioning in calling across the choruses in hours of darkness (after sunset) illustrates the complexity of monitoring communities of different vocal species. The study has outlined some of the patterns biological sounds exhibit, which has significant implications for sampling strategies when using soundscapes for temporal and spatial predictive modelling.